Comparative study on ship wave making resistance via viscous and IBEM solvers - Ozdemir, Yavuz Hakan; Cosgun, Taner; Barlas, Baris; Barlas, Barış (Elsevier BV, 2021)
Abstract The present paper concerns the numerical modeling of the free surface flow around the Wigley hull using viscous and potential flow based solvers over a range of Froude Numbers from 0.22 to 0.48. Numerical results of the in-house iterative boundary element method (IBEM) code and unsteady Reynolds Averaged Navier-Stokes (URANS) CFD tool presented in comparison with the range and average of the experimental data from the literature. The study aims to identify the Froude number envelope in which potential and viscous solvers work well, and match the results with the physical behavior of the flow. The results reveal that both methods are capable of predicting the wave-making resistance in satisfactory agreement with the experiments at intermediate Froude Numbers. IBEM exhibits slightly better accuracy at very low operating velocities. When the ship is advancing with a forward speed at Fn > 0.4, boundary layer separation related viscous effects and enhancing turbulence in the wake region of the hull cause the IBEM to underestimate the resistance. For low Fns, the deviation from the mean of the experimental data is 5% and 17% for IBEM and URANS, respectively, while the relative errors are calculated as 7% for URANS and 23% for IBEM at the highest Fn. Similarly, when the Fn reaches up to 0.4, the URANS method predicts higher values of wave climbing near the bow region compared to those of the potential solver, while the computations of both methods are very close at lower Fn. Besides these, IBEM enables a greater saving of computational time while reaching through the lower values of Fn. The findings of the study reveal that the present IBEM approach provides quick and reliable numerical solutions till the effect of viscous stress becomes non-negligible (which is Fn